IDENTIFIKASI PARAMETER FISIK MASSA, KEKAKUAN DAN REDAMAN DENGAN MENGGUNAKAN METODE ESTIMASI - Hutahaean, Ramses (MESIN, 2006)
Due to progressively expand ofthe complication machine structure, hence the accurate mathematicsmodels will become important in order machine structure design. But sometimes we found that themathematics modeling cannot forecast the dynamics behavior in comparison with real dynamicscharacteristic ofthe structure. Thatis becauseofinaccurate whendetermining the parameter whenmodellingprocess. In order to get the real dynamics characteristic, we need a teqnique to identify the dynamicscharacteristic of the structure by measuringfrequency respon function, while the constraint often is verydifficult to get the damping matrix from data containing noise. At this handing out method, writer willestimate mass, stiffness and damping matrix which developed by Chen, Ju And Tsuei (1996) to determinedynamics characteristic ofrotating rotor.